PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERDASARKAN KERANGKA KERJA TPACK PADA MATERI LINGKARAN UNTUK MENGOPTIMALKAN KEMAMPUAN PENALARAN DEDUKTIF - gusnidar gusnidar; Sutrisno Sutrisno; Syaiful Syaiful (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
AbstractTPACK workframe development research on the Curved Plane Solids is intended to develop a workframe such as Learning Plan (RPP) and students’ activity sheets (LKPD) in the form of a flip page ebook, apply the workframe and analyze the relantionship among components of TPACK compiler. Student test scores on average 77 wich includes the category of “optimal”..